1998
DOI: 10.1007/bf03028809
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide in chronic progressive multiple sclerosis: a comparative study

Abstract: No effective treatment is presently available for progressive multiple sclerosis (MS). Cyclophosphamide (CFX), a cytotoxic immunosuppressive drug widely used in systemic dysimmune diseases, has been proposed for the treatment of multiple sclerosis with different schedules and controversial results. To evaluate the safety and clinical efficacy of CFX, we compared three different treatment schedules in patients with progressive MS: induction followed by bimonthly boosters for one year (17 patients); bimonthly bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…La Mantia et al reported in 30 progressive patients a better response in relapsing-progressive patients and in those receiving induction plus boosters (600 mg/m 2 ) every 2 months for 12 months. 55 Manova et al reported improved responses on disability at 12 months in 70 patients with acute relapses treated with a 3-month course of cyclophosphamide plus methylprednisolone versus methylprednisolone clone. 51 With the widespread use of beta-interferon and glatiramer acetate, physicians have been confronted with refractory patients and have reported positive results following treatment with cyc loph os ph amide in op en-label studies.…”
Section: The Canadian Cooperative Study and The Kaiser Studymentioning
confidence: 99%
“…La Mantia et al reported in 30 progressive patients a better response in relapsing-progressive patients and in those receiving induction plus boosters (600 mg/m 2 ) every 2 months for 12 months. 55 Manova et al reported improved responses on disability at 12 months in 70 patients with acute relapses treated with a 3-month course of cyclophosphamide plus methylprednisolone versus methylprednisolone clone. 51 With the widespread use of beta-interferon and glatiramer acetate, physicians have been confronted with refractory patients and have reported positive results following treatment with cyc loph os ph amide in op en-label studies.…”
Section: The Canadian Cooperative Study and The Kaiser Studymentioning
confidence: 99%
“…There was no statistically significant difference in clinical results for SPMS and PPMS, although the numbers of PPMS patients were small in each study. The percentage of patients worsening in the La Mantia et al study [26] is higher than one finds in natural history studies in MS [29]. In the Hohol et al study [27], patients who improved had a progressive course for a shorter time then those who did not improve.…”
Section: Cyclophosphamidementioning
confidence: 71%
“…In the La Mantia et al study, 10 of 53 (19%) of patients withdrew during the 1 year of treatment [26]. In the Hohol et al study, 22 of 95 (23%) of patients withdrew in year one, and 47 of 95 (49%) withdrew in year two [27].…”
Section: Cyclophosphamidementioning
confidence: 92%
See 2 more Smart Citations